Characterisation of mutations of the phosphoinositide-3-kinase regulatory subunit, PIK3R2, in perisylvian polymicrogyria: a next-generation sequencing study. Issue 12 (December 2015) - Mirzaa, Ghayda M; Conti, Valerio; Timms, Andrew E; Smyser, Christopher D; Ahmed, Sarah; Carter, Melissa; Barnett, Sarah; Hufnagel, Robert B; Goldstein, Amy; Narumi-Kishimoto, Yoko; Olds, Carissa; Collins, Sarah; et al.
Summary: Background: Bilateral perisylvian polymicrogyria (BPP), the most common form of regional polymicrogyria, causes the congenital bilateral perisylvian syndrome, featuring oromotor dysfunction, cognitive impairment, and epilepsy. The causes of BPP are heterogeneous, but only a few genetic causes have been reported. The aim of this study was to identify additional genetic causes of BPP and characterise their frequency in this population. Methods: Children (aged ≤18 years) with polymicrogyria were enrolled into our research programme from July, 1980, to October, 2015, at two centres (Florence, Italy, and Seattle, WA, USA). We obtained samples (blood and saliva) throughout this period at both centres and did whole-exome sequencing on DNA from eight trios (two parents and one affected child) with BPP in 2014. After the identification of mosaic PIK3R2 mutations in two of these eight children, we performed targeted screening of PIK3R2 by two methods in a cohort of 118 children with BPP. First, we performed targeted sequencing of the entire PIK3R2 gene by single molecule molecular inversion probes (smMIPs) on 38 patients with BPP with normal to large head size. Second, we did amplicon sequencing of the recurrent PIK3R2 mutation (Gly373Arg) in 80 children with various types of polymicrogyria including BPP. One additional patient had clinical whole-exome sequencing done independently, and was included in this study because of the phenotypic similarity to our cohort. Findings: We identified a mosaic mutation (Gly373Arg) in a regulatory subunit of the PI3K-AKT-mTOR pathway, PIK3R2, in two children with BPP. Of the 38 patients with BPP and normal to large head size who underwent targeted next-generation sequencing by smMIPs, we identified constitutional and mosaic PIK3R2 mutations in 17 additional children. In parallel, one patient had the recurrent PIK3R2 mutation identified by clinical whole-exome sequencing. Seven of these 20 patients had BPP alone, and 13 had BPP in association with features of the megalencephaly-polymicrogyria-polydactyly-hydrocephalus (MPPH) syndrome. 19 patients had the same mutation (Gly373Arg), and one had a nearby missense mutation (Lys376Glu). Mutations were constitutional in 12 patients and mosaic in eight patients. In patients with mosaic mutations, we noted substantial variation in alternate (mutant) allele levels, ranging from ten (3%) of 377 reads to 39 (37%) of 106 reads, equivalent to 5–73% of cells analysed. Levels of mosaicism varied from undetectable to 37 (17%) of 216 reads in blood-derived DNA compared with 2030 (29%) of 6889 reads to 275 (43%) of 634 reads in saliva-derived DNA. Interpretation: Constitutional and mosaic mutations in the PIK3R2 gene are associated with developmental brain disorders ranging from BPP with a normal head size to the MPPH syndrome. The phenotypic variability and low-level mosaicism, which challenge conventional molecular methods, have important implications for genetic testing and counselling. Funding: US National Institutes of Health.